Exploring the role of board characteristics in shapping corporate ESG performance: an empirical analysis - Bani-Khaled, S.M.; Azevedo, G.; Oliveira, J. (5th International Conference in Accounting and Finance Innovation, 2024)
This study examines the impact of board characteristics on Environmental, Social, and Governance (ESG) performance using a dataset of 4,803 firm year observations from companies listed on the STOXX Europe 600 index, covering the period from 2010 to 2022. This study addresses this gap in the literature by investigating the influence of specific board attributes, including gender diversity, independent board members, board size, CEO board membership, frequency of meetings, board-specific skills, and term duration, on ESG performance. The originality of this study lies in its comprehensive analysis and exploration of sector sensitivity as a moderating factor. The findings reveal that board characteristics significantly affect ESG performance. Specifically, gender diversity, independent board members, and board-specific skills positively contribute to sustainability efforts, while CEO board membership and longer-term durations are negatively associated with ESG performance. Additionally, larger boards tend to correlate with lower ESG performance. Further analysis indicates that board characteristics’ impact on ESG performance varies across sectors. The positive influence of independent board members is diminished in sectors characterised by heightened environmental and social risks. Conversely, larger boards in these sensitive sectors appear more effective in addressing ESG issues. The originality of this study lies in its integration of stakeholder and agency theories to explain how corporate governance can address stakeholder concerns and align management with sustainable practices. Future research should explore sector-specific governance strategies and their impacts on ESG performance. Practically, companies and policymakers can leverage these insights to enhance corporate sustainability by optimising governance structures. Tailored strategies that consider sector-specific dynamics are crucial for promoting effective and responsive ESG practices, ultimately leading to improved sustainability.